Analisis Kebutuhan Media Komik Digital untuk Meningkatkan Literasi Membaca bagi Siswa Sekolah Dasar di Bojonegoro - Dwi Wulandari; Triana Rejekiningsih; Eka Budhi Santosa (Departement of Mathematics Education, 2023)
Research on digital comics in an effort to increase reading literacy is urgent because there is boredom during the learning process. It is hoped that the integration of digital comics with learning materials can change students' perceptions of reading activities to be more positive. This research aims to explore the need for digital comics that can help students develop their reading literacy. This research uses mixed methods that combine quantitative and qualitative data. Quantitative data was obtained through questionnaires given to 24 elementary school students, while qualitative data was obtained through interviews with teachers involved in the learning process. The results of data analysis show that teachers still dominate the delivery of material and rarely use digital learning media. Students, on the other hand, have access to Android smartphones, but their use tends to be for entertainment rather than learning. Therefore, this research highlights opportunities for developing digital comics as a learning tool, considering students' interest in using them to understand lesson material at home.